Teachers’ Perspectives on Using Tory-Boo Animation Video in Teaching English Literacy to Young Learners - Zidni Ma'ruf; Munaja Rahma; Ahmad Khoirul Akhir Tanjung; Amanda Karmelita; Fransiska Amelia Tarigas; Rizky Aliansyah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to explore teachers' perspectives on the use of the animated video Tory-Boo in teaching English literacy to early childhood learners. This study used a descriptive qualitative method. Participants in this study were six English teachers who teach early childhood learners and have experience using animated videos in their classrooms. Data were collected using a semi-structured interview guide. All interview data were recorded and transcribed. The research data were analyzed and categorized into several themes. Member checking was also conducted to ensure the validity of the data. The results showed that teachers generally had a positive perspective on the use of the animated video Tory-Boo. The video was considered an engaging and effective learning medium that can increase student motivation, support vocabulary development, and enhance comprehension through visual and contextual input. In addition, the use of animated videos facilitated interactive and student-centered learning through various follow-up activities. However, several challenges were also identified, including technical constraints, classroom management, and the need to select content appropriate to students' language proficiency levels. This study suggests that animated videos can be a valuable tool in teaching English literacy when supported by appropriate pedagogical strategies.